Respuesta :

Answer:

[tex]g(x) = 6[/tex]

Step-by-step explanation:

Begin with substuting the x variable with -2, we do this because the question has listed the value of x already.

Using the value of x, -2 we determine g(x).

g(x) = -2^2 + 2

Above is what the equation would look as, after you input the value of -2.

Using pemdas, (parantheses, exponents, multiplication, division, addition, subtraction) solve the equation.

-2^2 = 4

Think of it as -2 * -2, which is why -2^2 is 4.

Add 4 +2.

4 + 2 = 6.

Therefore, the value of g(x) = 6